Proliferation And Elicitation Of Protocorm-Like Bodies Of Dendrobium Sabin Blue For In Vitro Production Of Anthocyanin - Malik, Aimie Nadzirah Abd (2019)
High demands for Dendrobium cut flowers as well as the secondary metabolite products lead to the over-exploitation of the orchid from its natural habitat. The use of in vitro hybrid orchid is one of a prominent strategy to meet the demand. Dendrobium Sabin Blue (a hybrid species between Dendrobium Blue Angel and Dendrobium Sanan Blue) orchid was used in this study to produce anthocyanin. The aim of this study is to improve in vitro proliferation of protocorm-like bodies (PLBs) of Dendrobium Sabin Blue and enhancing anthocyanin content by using elicitors. For PLBs proliferation, four different types of plant growth regulators (1-Naphthaleneacetic acid, 6-Benzylaminopurine, kinetin and picloram) with different concentrations were tested. The results revealed that 10 μM of NAA produced the highest growth index of PLBs with 10.947 ± 0.825 as compared to the control with only 1.67 ± 0.111. In addition, histological analysis showed a dense meristematic cell and presence of starch grains which indicates the actively growing of cell. In addition, a delicate technique was utilized to further promote a rapid and mass propagation of PLBs through in vitro culture of thin cell layer (TCL). After four weeks of culture, results showed that transverse TCL (tTCL) produced the highest number of PLBs with a total of 59 PLBs were produced from a single thin layer cut as compared to longitudinal TCL (lTCL). The tTCL also produced significantly higher number of shoots with 15 shoots as the highest record.